Minimum Fragments of the Heparin Molecule Able to Produce the Accumulation and Change of the Sulfation Pattern of an Antithrombotic Heparan Sulfate from Endothelial Cells - Pinhal, Maria A S; Santos, Isabel A N; Silva, Irani F; Dietrich, Carl P; Nader, Helena B (Thrombosis and Haemostasis, 1995)
Heparin and low molecular weight heparins stimulate two to three fold the accumulation of an antithrombotic heparan sulfate secreted by endothelial cells in culture. This led us to search for the minimum structural requirements of the heparin molecule able to elicit the enhancement of the heparan sulfate. Fragments were prepared from heparin by degradation with bacterial heparinase and heparitinases. A heparin pentasulfated tetrasaccharide was shown to be the minimum structural sequence able to enhance two to three fold the secretion of heparan sulfate by endothelial cells. The stimulation is specific for the endothelial cell, is concentration dependent and the effect is already noticed afterone hour of exposure of the cells to heparinand the tetrasaccharide. Degradation of the [35S]-heparan sulfate synthesized in the presence of heparin or the tetrasaccharide has shown a higher degree of sulfation of its iduronic acid residues.